PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VII MTS MUHAMADIYAH BAGANSIAPIAPI TAHUN PELAJARAN 2015/2016 - Jumarni, Emi Rusira; Linggasari, Mariani Natalina; ', Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is a classroom action research that aims to improve the learning outcomes of students in IPA class VII MTs Muhammadiyah Bagansiapiapi in the academic year 2015/2016 with the adoption of kooperatip STAD learning model. The study was conducted in March-April 2016. The subjects were students of class VII MTs Muhammadiyah Bagansiapiapi totaling 28 people (15 students and 13 female students). Parameters measured are student learning outcomes consisting of absorption, mastery learning students individually, Value awards groups, student activities and teacher activity by giving a score on each indicator diobservari by the observer.Absorptive capacity based on the post-test on the first cycle petemuan 1 is 75% (enough) and increases at a meeting of 2 to 79.6%, while in the second cycle, meeting 1 was 83.6% (good) and increased to 88.2%. Mastery learning students based upon a daily test on the first cycle ie 77.78% (enough) and the second cycle increased to 88.07% (excellent).Group awards in the first cycle, one predicated super group and4 great predicated group. In the second cycle, the 2 groups and 3 groups predicated predicated super great. Learning activities of students during a discussion with the implementation of cooperative learning model STAD first cycle increased in the first cycle that 81.11 % (Good) increased to 89.73% (excellent) on the second cycle. Activities teachers in the learning process in the first cycle was 88.45%, (good) and the second cycle was 96.15% (excellent). It can be concluded that the implementation of cooperative learning model STAD can improve learning outcomes IPA class VII MTs Muhammadiyah Bagansiapiapi the school year 2015/2016.Keywords : STAD cooperative mode, IPA Learning Outcomes